Evaluation of Plastic Grain Engulfment Rescue Device - Kingman, Douglas M.; Muller, Joe E.; Nelson, Kara N. (Journal of Agricultural Systems, Technology, and Management, 2007)
Full and partial engulfment incidents in free-flowing grain and other loose materials continue to occur and are documented each year in newspapers, university and federal safety literature, and by other surveillance activities. Although a grain rescue tube design made from stainless steel has existed since the 1980s, it was determined that it was not suitable for use in all or most partial engulfment situations. Specifically, the major components of the tube were not able to be passed through small openings typically associated with on-farm grain bins and even some commercial storage facilities. During rescue demonstration activities at such facilities, it was learned that the tube weighed in excess of 180 pounds and was difficult to insert into a grain mass. In order to address the rescue of a partially engulfed individual, a rescue tube made from PVC plastic pipe was constructed and evaluated in a bin of shelled corn. It was concluded that the plastic tube had some features that were beneficial. The sliding tube sections allowed easy insertion into the grain, lightweight components facilitated handling and lifting, and tube sections fit easily through small openings associated with on-farm storage structures. Recommendations suggested that further development and testing is warranted. Additional work should explore the use of tube sections made from ultra high molecular weight (UHMW) plastic and inserting the tube sections in other bulk materials such as sand, granular fertilizer, salt, and rock.